Up-regulation of GLT-1 severely impairs LTD at mossy fibre–CA3 synapses - Omrani, Azar (Blackwell Science Inc, 2009)
Glutamate transporters are responsible for clearing synaptically released glutamate from the extracellular space. By this action, they maintain low levels of ambient glutamate, thus preventing excitotoxic damage, and contribute to shaping synaptic currents. We show that up-regulation of the glutamate transporter GLT-1 by ceftriaxone severely impaired mGluR-dependent long-term depression (LTD), induced at rat mossy fibre (MF)–CA3 synapses by repetitive stimulation of afferent fibres. This effect involved GLT-1, since LTD was rescued by the selective GLT-1 antagonist dihydrokainate (DHK). DHK per se produced a modest decrease in fEPSP amplitude that rapidly regained control levels after DHK wash out. Moreover, the degree of fEPSP inhibition induced by the low-affinity glutamate receptor antagonist γ-DGG was similar during basal synaptic transmission but not during LTD, indicating that in ceftriaxone-treated rats LTD induction did not alter synaptic glutamate transient concentration. Furthermore, ceftriaxone-induced GLT-1 up-regulation significantly reduced the magnitude of LTP at MF–CA3 synapses but not at Schaffer collateral–CA1 synapses. Postembedding immunogold studies in rats showed an increased density of gold particles coding for GLT-1a in astrocytic processes and in mossy fibre terminals; in the latter, gold particles were located near and within the active zones. In both CEF-treated and untreated GLT-1 KO mice used for verifying the specificity of immunostaining, the density of gold particles in MF terminals was comparable to background levels. The enhanced expression of GLT-1 at release sites may prevent activation of presynaptic receptors, thus revealing a novel mechanism by which GLT-1 regulates synaptic plasticity in the hippocampus.